Implementation of Fun Learning Strategy to Increase Students' Motivation in Learning Christian Religious Education at SMP YPPGI Sentani - Kada Kaka, Murniyati Sampe; Pentury, Jolanti W.; Butu, Dorce (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyse the application of Fun Learning strategy in increasing students' motivation in learning Christian Religious Education (PAK) at SMP YPPGI Sentani. The background of this research departs from the low motivation of students to learn due to the use of monotonous and less interactive learning methods. This research uses a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, then analysed using an interactive model. The results showed that the application of Fun Learning through prayer and singing simulation activities, group discussions, and educational games such as Quizizz succeeded in increasing students' motivation, participation, and confidence. Students became more enthusiastic, active, and had a deeper understanding of the value of faith. In conclusion, the Fun Learning strategy is effective in creating a fun learning atmosphere, increasing intrinsic motivation, and integrating faith values with meaningful learning experiences.